PENGUATAN KOMPETENSI GURU SMK MELALUI PELATIHAN PEMERIKSAAN HASIL PENGELASAN BERSTANDAR AWS - Putra, Ananda Yhuto Wibisono; Abdillah, Hamid; Janata, Ade Dwi Putra; Putra, Ricky Cahyasari; Fawaid, Moh; Febriyanto, Rusdi; Ikhsanudin, Ikhsanudin (Universitas Mataram, 2025)
Vocational education requires teachers to possess professional competencies that are relevant to industrial developments, including skills in weld inspection. However, most vocational high school (SMK) teachers still face limitations in understanding inspection procedures based on international standards. This condition creates a gap between the teaching process and the needs of industry, which emphasizes weld quality. Therefore, a systematic training program is needed to improve the quality of welding instruction in vocational schools. This activity aimed to strengthen the competencies of vocational school teachers in conducting weld inspections according to the American Welding Society (AWS) standards. The methods included needs assessment, delivery of theoretical materials, practice of visual inspection and non-destructive testing (NDT), as well as process and outcome evaluation. The training was implemented in a participatory manner through a combination of lectures, discussions, and hands-on practice with experienced instructors. The results indicated that teachers gained better conceptual understanding of weld inspection standards. Moreover, their technical skills in visual inspection and the application of NDT methods improved significantly. Process evaluation showed active participation and high enthusiasm among participants, while outcome evaluation demonstrated high levels of satisfaction with the instructors’ competence and the relevance of the materials to school practices. Overall, the training effectively bridged teachers’ competency gaps and enhanced the relevance of vocational learning to industry standards.